Forecasting for the Investment Project Appraisal - Szpulak, Aleksandra (Rola prognozowania w ocenie projektów inwestycyjnych, 2009)
Financial managers almost always act in the conditions of uncertainty. Their two essential tasks – funds allocation within the enterprise and funds rising – are both concerned with the future events. Besides, only effective allocation of company’s funds primary financed by the best (in certain conditions) available sources is a company’s maximization value factor. (fragment of text)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 48, s. 785-793